2019
DOI: 10.1111/sjop.12535
|View full text |Cite
|
Sign up to set email alerts
|

Incivility at work, upset at home? Testing the cross‐level moderation effect of emotional dysregulation among female nurses from primary health care

Abstract: 2019). Incivility at work, upset at home? Testing the cross-level moderation effect of emotional dysregulation among female nurses from primary health care. Scandinavian Journal of Psychology, 60, 267-276.Workplace incivility is a growing problem in nursing. However, most studies that explore this psychosocial risk and its consequences do so considering a single level and a between-person perspective. The aims of the study were to explore whether the effects of experiencing incivility during work-time could ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, it is important to note there is a positive correlation between burnout, withdrawal and absenteeism among healthcare workers who have experienced WPB. [7][8][9] Research has also shown turnover rates as high as 60%…”
Section: Ta B L E 1 Demographics and Work Characteristics (N = 765)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note there is a positive correlation between burnout, withdrawal and absenteeism among healthcare workers who have experienced WPB. [7][8][9] Research has also shown turnover rates as high as 60%…”
Section: Ta B L E 1 Demographics and Work Characteristics (N = 765)mentioning
confidence: 99%
“…There is a significant relationship between WPV and absenteeism in the workplace, 7 work-related burnout 8 and the negative effects it has on home life. 9 In addition, WPV impacts mental and physical health, employee turnover, retention rates and patient satisfaction. 10 Studies have shown turnover rates as high as 60% in healthcare workers on the receiving end of WPV.…”
mentioning
confidence: 99%
“…In a future study, we could examine whether overt incivility is masculine/agentic characterized whereas covert incivility is associated to feminine/communal stereotype, as we suspect from our results. Moreover, this experiment focused on a male domain, thus, we recommend extending the study to the female domain (i.e., nursing) to compare the effects in both gender domains following a recent line of research on this topic (Blanco‐Donoso, Amutio, Moreno‐Jiménez, Yeo‐Ayala, Hermosilla & Garrosa, ). Introducing these suggestions in future research on incivility and gender could provide greater control to the experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…A study of critical care nurses in Iran showed that ER training was effective in decreasing occupational stress . Furthermore, it was found that nurses who had difficulty coping or regulating emotions at work experienced depersonalization and emotional exhaustion after work . This negative effect seemed to be higher among nurses with fewer job resources at work .…”
Section: Uses Of the Ermentioning
confidence: 99%
“…Furthermore, it was found that nurses who had difficulty coping or regulating emotions at work experienced depersonalization and emotional exhaustion after work . This negative effect seemed to be higher among nurses with fewer job resources at work . Studies on ER strategies suggested that dispositional mindfulness may have a direct influence on nurses’ working memory capacity, cognitive ER was associated with decreased depersonalization (Bamonte et al, 2017), and positive ER strategies could promote well‐being outside of work .…”
Section: Uses Of the Ermentioning
confidence: 99%